SCIENTIFIC EDUCATIONAL ELECTRONIC LIBRARIES IN EDUCATING INFORMATIONAL SYSTEMS AND TECHNOLOGIES OF FUTURE MANAGERS - Nataliia S. Prilutska; Oksana I. Yatsenko (Information technologies and learning tools, 2013)
The article deals with the main principles of electronic libraries. It analyzes primary types of digital scientific and educational resources, presented in electronic libraries and defines the techniques of effective structuring of the learning content by means of informational technologies in the conditions of the informational processes intensification. The scientific fundamentals of choice of educational material are determined and the structure of the educational subject ''Informational Systems and Technologies'' under the credit and module system are designated. The declared structure of educational subject is taught for the students of the social-pedagogical department, referral courses ''Management''.